PENGALAMAN KELUARGA DALAM MELAKUKAN PENCEGAHAN PENULARAN TB DI KELURAHAN MATAWAI WILAYAH KERJA PUSKESMAS WAINGAPU KABUPATEN SUMBA TIMUR - GUNAWAN, YOSEPHINA E.S.; INA, ELSIANA TAMO (Poltekkes Kemenkes Kupang, 2017)
Introduction: The incidence of Tuberculosis provides its own experience against a family member who is a member of his family is a TB sufferer, the impact of TB disease that is the presence of negative feelings and positive feelings in felt by family members as well as the perception that says TB are not infectious.Gain an in-depth overview of the experiences of family members caring for TB patients.Method: The research design used was the qualitative approach with Phenomenology. Five participants selected by the technique of purposive sampling, with interviews of family members experience caring for/do prevention of transmission of TB.Result: In this research obtained three themes, namely the feelings of family members caring for/do prevention of the transmission of TB, the role of family members caring for TB patients and family obstacle in conducting prevention transmission of TB.Conclusion: It was concluded that a family member had a negative and positive feelings, the less understanding, and barriers experienced within the family.It is recommended that TB sufferer's family members put themselves as part of the community, increasing their role in live as PMO well and to the nursing community in particular in Waingapu of clinics in order to improve the service of TB sufferers with treatment and care holistically i.e biopsikososial and spiritual.